Analisis Pengaruh Kecerdasan Emosional, Organizational Citizenship Behavior, dan Komitmen Organisasi terhadap Kinerja Karyawan pada Supermarket Citra Siantan di Pontianak - Miranda Miranda (LPPM Universitas Widya Dharma Pontianak, 2025)
This study aims to determine the influence of emotional intelligence, organizational citizenship behavior, and organizational commitment on employee performance at the Citra Siantan Supermarket in Pontianak. The research used an associative approach, using a questionnaire as the data collection method. The measurement scale used was a Likert scale. The population in this study was 55 employees, and the sampling technique used was saturated sampling. The data obtained were tested using SPSS version 23 software. The data testing methods used were validity, reliability, normality, multicollinearity, heteroscedasticity, linearity, multiple linear regression, coefficient of determination, f-test, and t-test. The results showed that (1) emotional intelligence had a positive and significant effect on employee performance, (2) organizational citizenship behavior had a positive and significant effect on employee performance, (3) organizational commitment had a positive and significant effect on employee performance, (4) emotional intelligence, organizational citizenship behavior, and organizational commitment simultaneously had a positive and significant effect on employee performance.